THE CORRELATION BETWEEN MOTIVATION AND LEARNING OUTCOMES IN ENGLISH CLASS: (A Study at Arabic Education Students) - Zahrina (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The study was conducted to identify whether there was a correlation between motivation and students’ achievements in learning English. It took 17 of Arabic Education students as the sample of this research. The technique of data collection was done by using test, interview and questionnaire. The result of the study revealed that motivation influenced and contributed the positive correlation in learning outcomes of the students’. It was obviously seen through the relation between the test given and motivation scales and also supported by the students’ clarification via interview and questionnaire.